Nigella sativa improves the carbon tetrachloride-induced lung damage in rats through repression of erk/akt pathway - Aslan, Abdullah; Boydak, Didem; Can, Muhammed Ismail; Kuloglu, Tuncay (Bangladesh Pharmacological Soc, 2015)
The objective of this study was to examine whether Nigella sativa plays a protective role against the damage in the lung by administering carbon tetrachloride (CCl4) to rats. Male Wistar albino (n= 28, 8 weeks old) rats were divided into 4 groups: a) negative control: Normal water consuming group to which no CCl4 and N. sativa was administered; b) Positive control: Normal water consuming group to which no CCl4 was administered but N. sativa was administered; c) CCl4 Group: Normal water consuming and group to which CCl4 was administered (1.5 mL/kg, ip); d) N. sativa plus CCl4 group: CCl4 and N. sativa administered group (1.5 mL/kg, ip). Caspase-3, caspase-9, erk, akt protein syntheses were examined via Western blotting. Malondialdehyde determination in lung tissue was made using spectrophotometer. As a results, malondialdehyde amount was decreased in the CCl4 plus N. sativa group in comparison to CCl4 group whereas caspase-3, caspase-9 was increased and erk, akt had decreased. These results show that N. sativa protects the lung against oxidative damage.
Keywords: Oxidative Stress; Nrf2/Ho-1; Oil; Suppression; Impedes; Extract; Juice; Acid; Seed